A novel microfluidic 3D platform for culturing pancreatic ductal adenocarcinoma cells: comparison with in vitro cultures and in vivo xenografts - Meike Beer (Nature Portfolio, 2017)
Abstract The integration of microfluidics and cell biology has reached a significant milestone with the development of “organ-on-chips”, smart technological platforms that, once applied to the study of human diseases, such as cancer, might ultimately contribute to design personalised treatments and hence improve health outcomes. This paper reports that the combination of microfluidics and dielectrophoresis (DEP) allows to culture different pancreatic ductal adenocarcinoma (PDAC) human cell lines into a cyclic olefin polymer (COP) chamber (HepaChip®), enriched by the extracellular matrix (ECM) protein collagen. We show that PDAC cells cultured into the HepaChip® (1) are vital and grow, provided they properly attach to collagen; (2) show morphological appearance and growth characteristics closer to those of cells grown as spheroids than as classical 2 dimensional (2D) in vitro cultures. Finally, preliminary experiments show that PDAC cells respond to high doses of Cisplatin perfused through the chip. Overall, the present microfluidic platform could be exploited in the future for a personalised approach to PDAC.